Frequency of Multi-drug Resistant (MDR), Extensive Drug Resistant (XDR) and Extended-spectrum β-lactamase (ESBL) Salmonella in Culture Positive Patients of Enteric Fever - Ali, Armaghan; Gillani, Saima; Aziz, Noor; Khalid, Komal; Adnan, Mian Sohail; Khan, Salman (Indus Journal of Bioscience Research, 2025)
Introduction: Typhoid fever, the disease caused by Salmonella enterica serotypes Typhi and Paratyphi, is still prevalent in Pakistan, and it is observed that an increasing proportion of isolates are resistant to antimicrobial drugs. The increased rates of MDR, XDR, and ESBL-producing Salmonella isolates further aggravate the problem of treatment and controlling the infection. Objectives: The purpose of the study was to know the frequency of MDR, XDR and ESBL-producing Salmonella strains in culture-positive enteric fever patients in Ayub Teaching Hospital, Abbottabad. Materials and Methods: The cross-sectional study was conducted from 14 September, 2024 to 13 March, 2025 at Ayub Teaching Hospital, Abbottabad. The samples were cultured for Salmonella strains, and antibiotic resistance was determined to determine MDR, XDR, and ESBL production. Results: A total of 45% were resistant to at least one antibiotic class, 17% were resistant to at which are referred to as extensively drug-resistant, and 4.47% produced extended-spectrum beta-lactamase enzymes. MDR and XDR strains were identified in the children who were either non-vaccinated or those with a longer duration of fever. Conclusion: The study portrays the increased emergence of these resistant strains of Salmonella that require better vaccination, antibiotics administration and control, and better hygienic measures.